Real Time Domestic Power Consumption Monitoring using Wireless Sensor Networks - Venkatsampath Raja Gogineni; Kalyan Matcha; Raghava Rao K (Institute of Advanced Engineering and Science, 2015)
This paper subsumes the implementation of automation in tracking the electrical consumption data of household systems over the network (WEB). This could sub-sequentially cut down the manual work involved in the process of collecting no: of units consumed from each house, thereby avoiding the manual costs and errors by building an automatic network access. The installation of this system is quite an easy task, which do not need much hardware work. The key elements that make this system are Current sensor and Voltage sensor interfaced to an Arduino board (A General Purpose Micro Controller board) with an Ethernet shield and a WIFI Router for transmission of data wirelessly to the server for storing consumption values into the database. Hosting web pages with the database connectivity will make the administrator generate electricity bill automatically that facilitates user’s to view and pay his electricity bill online.